Sexual harassment faced by women on the streets : is it a problem? (a Singaporean based context). - Loh, Bernice Kit Teng. (2013)
This study is conducted to investigate the extent to which Singaporean young women, between the ages of 21-25, experience gender based street harassment. The various types of harassing behaviours will be explored and discussed. The consequential responses and emotions of the victims will be revealed too. In addition, these girls do employ consciously strategies of actions to guard against harassers. The data collected give insights into one’s resultant sense of self and their perceptions of men and their general view of society. This research seeks to highlight the severity of stranger harassment and the limited lines of action and enforcement on this issue.